Obesogenic eating behaviour and dietary intake in German children and adolescents: results from the GINIplus and LISA birth cohort studies - Marb, Anne; Libuda, Lars; Standl, Marie; Koletzko, Sibylle; Bauer, Carl-Peter; Schikowski, Tamara; Berdel, Dietrich; von Berg, Andrea; Herberth, Gunda; Bühlmeier, Judith; Harris, Carla P. (European Journal of Clinical Nutrition)
Abstract Background/objectives The transition to adolescence is characterised by considerable behavioural changes, including diet. This study describes the level of obesogenic eating behaviours in 10- and 15-year-olds, and their association with dietary intake. Subjects/methods Participants of the 10- and 15-year follow-ups of the German GINIplus and LISA birth cohort studies were included (N 10 = 2257; N 15 = 1880). Eating behaviours and dietary intake were assessed via self-report questionnaires. Sex-stratified, cross-sectional associations of “external eating”, “emotional eating” and “dietary restraint” (the latter at age 15 years only) with dietary intake (17 food groups—categorised into tertiles, macronutrients, and total energy) were assessed using multinomial logistic or multiple linear regression as required, adjusting for covariates and correcting for multiple testing. Results Reported levels of eating behaviours were low in both age-groups. External eating was higher in 10-year-old males than females, while all eating behaviours were most pronounced in 15-year-old females. At 10 years, emotional eating was associated with medium vegetable intake in females (Relative Risk Ratio (RRR) = 1.84, p = 0.0017). At 15 years, external eating was associated with total energy (kJ) in females ( β = 718, p = 0.0002) and high butter intake in males (RRR = 1.96, p = 0.0019). Dietary restraint in females was inversely associated with total energy ( β = −967, p < 0.0001) and omega-3 fatty acids (Means Ratio (MR) = 0.94, p = 0.0017), and positively associated with high fruit (RRR = 2.20, p = 0.0003) and whole grains (RRR = 1.94, p = 0.0013). Conclusion Obesogenic eating behaviour scores are low among children and adolescents of a predominantly high socioeconomic status population and present only few associations with specific aspects of diet, mainly among adolescent females.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Selective Area Growth of Cubic Gallium Nitride in Nanoscopic Silicon Dioxide Masks - Meier, Falco; Littmann, Mario; Bürger, Julius; Riedl, Thomas; Kool, Daniel; Lindner, Jörg; Reuter, Dirk; As, Donat Josef (physica status solidi (b))
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Sixteen-week multicentre randomised controlled trial to study the effect of the consumption of an oat beta-glucan-enriched bread versus a whole-grain wheat bread on glycaemic control among persons with pre-diabetes: a study protocol of the CarbHealth study - Hjorth, Therese; Schadow, Alena; Revheim, Ingrid; Spielau, Ulrike; Thomassen, Lise M; Meyer, Klara; Piotrowski, Katja; Rosendahl-Riise, Hanne; Rieder, Anne; Varela, Paula; Lysne, Vegard; Ballance, Simon; et al. (BMJ Open)
Introduction In 2012, the estimated global prevalence of pre-diabetes was 280 million, and the prevalence is expected to rise to 400 million by 2030. Oat-based foods are a good source of beta-glucans, which have been shown to lower postprandial blood glucose. Studies to evaluate the effectiveness of the long-term intake of beta-glucan-enriched bread as part of a habitual diet among individuals with pre-diabetes are needed. Therefore, we designed a multicentre intervention study in adults with pre-diabetes to investigate the effects of consumption of an oat-derived beta-glucan-enriched bread as part of a normal diet on glycated haemoglobin (HbA1c) in comparison to consumption of whole-grain wheat bread. Methods and analysis The CarbHealth trial is a multicentre double-blind randomised controlled 16-week dietary intervention trial in participants 40–70 years of age with a body mass index of ≥27 kg/m 2 and HbA1c of 35–50 mmol/mol. The study is conducted at four universities located in Norway, Sweden and Germany and uses intervention breads specifically designed for the trial by Nofima AS. The aim is to recruit 250 participants. The primary outcome is the difference in HbA1c between the intervention and the control groups. The main analysis will include intervention group, study centre and baseline HbA1c as independent variables in an analysis of covariance model. Ethics and dissemination The study protocol was approved by respective ethical authorities in participating countries. The results of the study will be communicated through publication in international scientific journals and presentations at (inter)national conferences. Trial registration number NCT04994327 .
Keywords: General Medicine

Correction: Short-term effects of carbohydrates differing in glycemic index (GI) consumed at lunch on children's cognitive function in a randomized crossover study. - Jansen, K; Tempes, J; Drozdowska, A; Gutmann, M; Falkenstein, M; Buyken, Anette; Libuda, Lars; Rudolf, H; Lücke, T; Kersting, M (Eur J Clin Nutr)

Health relevance of lowering postprandial glycaemia in the paediatric population through diet': results from a multistakeholder workshop. - Vinoy, S; Goletzke, J; Rakhshandehroo, M; Schweitzer, L; Flourakis, M; Körner, A; Alexy, U; van Schothorst, EM; Ceriello, A; Zakrzewski-Fruer, JK; Buyken, Anette (Eur J Nutr)

The adrenal steroid profile in adolescent depression: a valuable bio-readout? - Hirtz, Raphael; Libuda, Lars; Hinney, Anke; Föcker, Manuel; Bühlmeier, Judith; Holterhus, Paul-Martin; Kulle, Alexandra; Kiewert, Cordula; Hauffa, Berthold P.; Hebebrand, Johannes; Grasemann, Corinna (Translational Psychiatry)
Abstract There is preliminary evidence that adrenal steroids other than cortisol may be valuable biomarkers for major depressive disorder (MDD). So far, studies have been conducted in adults only, and conclusions are limited, mainly due to small sample sizes. Therefore, the present study assessed whether adrenal steroids serve as biomarkers for adolescent MDD. In 261 depressed adolescents (170 females) treated at a single psychiatric hospital, serum adrenal steroids (progesterone, 17-hydroxyprogesterone, 21-deoxycortisol, 11-deoxycortisol, cortisol, cortisone, deoxycorticosterone, corticosterone) were determined by liquid chromatography-tandem mass spectrometry. Findings were compared to that of an age- and sex-matched reference cohort ( N = 255) by nonparametric analysis of variance. Nonparametric receiver operating characteristics (ROC) analyses were conducted to evaluate the diagnostic performance of single steroids and steroid ratios to classify depression status. Sensitivity analyses considered important confounders of adrenal functioning, and ROC results were verified by cross-validation. Compared to the reference cohort, levels of deoxycorticosterone and 21-deoxycortisol were decreased ( P < 0.001). All other glucocorticoid- and mineralocorticoid-related steroids were increased ( P < 0.001). The corticosterone to deoxycorticosterone ratio evidenced excellent classification characteristics, especially in females (AUC: 0.957; sensitivity: 0.902; specificity: 0.891). The adrenal steroid metabolome qualifies as a bio-readout reflecting adolescent MDD by a distinct steroid pattern that indicates dysfunction of the hypothalamus–pituitary–adrenal axis. Moreover, the corticosterone to deoxycorticosterone ratio may prospectively qualify to contribute to precision medicine in psychiatry by identifying those patients who might benefit from antiglucocorticoid treatment or those at risk for recurrence when adrenal dysfunction has not resolved.
Keywords: Biological Psychiatry; Cellular and Molecular Neuroscience; Psychiatry and Mental health

Emotionale Erfahrungen von Lehramtsstudierenden bei der Arbeit mit Eigenvideografien von Unterricht – Fallanalysen aus einer längsschnittlichen Interviewstudie im Praxissemester - Pollmeier, Pascal; Rogge, Tim; Vogelsang, Christoph (ZeHf – Zeitschrift für empirische Hochschulforschung)
Die Arbeit mit Videografien eigenen Unterrichts wird in Praxisphasen in der universitären Lehramtsausbildung zunehmend als methodisches Mittel zur Reflexion von Unterrichtserfahrungen genutzt. Als wesentlicher Einflussfaktor für einen erfolgreichen Einsatz werden dabei die begleitenden Emotionen der Studierenden angenommen. In einer längsschnittlichen Interviewstudie wurden daher die emotionalen Prozesse von 20 Lehramtsstudierenden bei der Arbeit mit Eigenvideografien in Begleitveranstaltungen des Praxissemesters untersucht. Dabei konnten drei Typen rekonstruiert werden, die prototypische emotionale Muster im Praxissemesterverlauf beschreiben, die durch die Valenz emotionaler Zustände bezüglich der Eigenvideografie zu Beginn und Ende des Praxissemesters charakterisiert werden können (negativ-positiv, positiv-positiv, negativ-negativ). Bei fallübergreifender Betrachtung konnten zudem zentrale Zusammenhänge zwischen Emotionen und Merkmalen des Videoeinsatzes identifiziert werden, wie die Vertrautheit mit Mitstudierenden, der Prozess der Aufnahmegenehmigung und Vorerfahrungen mit Eigenvideografie. Die Ergebnisse der Studie können zur Vermeidung intensiver negativer Emotionen bei der Nutzung videobasierter Reflexion eigenen Unterrichts beitragen und die Akzeptanz von Eigenvideografie zur eigenen Professionalisierung in der Lehrerbildung erhöhen.

Entwicklung von Unterrichtsplanungsfähigkeit im Fach Physik: Welchen Einfluss hat Professionswissen? - Riese, Josef; Vogelsang, Christoph; Schröder, Jan; Borowski, Andreas; Kulgemeyer, Christoph; Reinhold, Peter; Schecker, Horst (Zeitschrift für Erziehungswissenschaft)
Zusammenfassung Im Lehramtsstudium sollen Studierende grundlegende Fähigkeiten zur theoriegeleiteten Unterrichtsplanung erwerben. In Übereinstimmung mit Modellen zur professionellen Handlungskompetenz von Lehrkräften wird hierbei meist angenommen, dass das im Studienverlauf erworbene Professionswissen eine wesentliche Grundlage für den Aufbau von Fähigkeiten zur Unterrichtsplanung bildet. Lerngelegenheiten zur Anwendung dieses Professionswissens bieten vor allem schulpraktische Phasen im fortgeschrittenen Studienverlauf. Es wird aber ebenso angenommen, dass gerade Erfahrungen mit der Unterrichtsplanung den Aufbau von Professionswissen unterstützen. Der Zusammenhang zwischen dem Ausmaß des Professionswissens und der Entwicklung von Planungsfähigkeit ist bisher unzureichend empirisch geklärt. Eine besondere methodische Herausforderung besteht darin, Planungsfähigkeiten sowohl möglichst authentisch als auch auf standardisierte Weise zu erfassen. Zur Untersuchung des genannten Zusammenhangs wurde eine längsschnittliche Studie im Prä-Post-Design bei angehenden Physiklehrkräften ( N = 68 im Längsschnitt) an vier Universitäten durchgeführt. Die Unterrichtsplanungsfähigkeit wurde mit Hilfe eines standardisierten Performanztests vor und nach dem Absolvieren eines Praxissemesters erfasst, indem als Standardsituation der Entwurf einer Unterrichtsstunde zum 3. Newton’schen Axiom unter definierten Zeitvorgaben im Praxissemester simuliert wurde. Zusätzlich wurden das fachliche, fachdidaktische und pädagogische Wissen der Studierenden mit Hilfe standardisierter Instrumente zu beiden Zeitpunkten erhoben, sowie die einschlägigen Lerngelegenheiten im Praxissemester über einen Fragebogen erfasst. Sowohl für Unterrichtsplanungsfähigkeit als auch für alle Wissensvariablen können Zuwächse im Praxissemester beobachtet werden. Cross-Lagged-Panel-Analysen zeigen, dass insbesondere die Ausprägung des fachdidaktischen und pädagogischen Wissens der Studierenden am Beginn des Praxissemesters die Entwicklung von Unterrichtsplanungsfähigkeit begünstigt.
Keywords: Education

Nutzungsverhalten von Lehrkräften bei der Implementierung einer physikdidaktisch innovativen Unterrichtskonzeption - Breuer, Judith; Vogelsang, Christoph; Reinhold, Peter (Zeitschrift für Didaktik der Naturwissenschaften)
Zusammenfassung Eine zentrale Aufgabe fachdidaktischer Forschung stellt die Verbesserung schulischen Unterrichts dar. Die freie Bereitstellung wirksamer Unterrichtskonzeptionen zur Unterstützung des Selbststudiums von Lehrkräften bildet eine Strategie für eine flächendeckende Implementierung fachdidaktischer Innovationen. Allerdings etablieren sich zahlreiche, empirisch erfolgreich evaluierte Unterrichtskonzeptionen nicht nachhaltig an Schulen. Daher untersucht das vorliegende Forschungsvorhaben den Implementationsprozess solcher Materialien unter authentischen Bedingungen. Dazu wurde kriteriengeleitet eine evidenzbasierte, fachdidaktisch innovative Unterrichtskonzeption ausgewählt: das Münchener Unterrichtskonzept zur Quantenmechanik (MILQ). Diese wurde den teilnehmenden Lehrkräften fakultativ zur Verfügung gestellt. Mittels Fallstudien wurde die Implementierung von MILQ von elf Lehrkräften durch halbstandardisierte Interviews zu Beginn und am Ende einer Unterrichtsreihe zur Quantenmechanik sowie zwei Unterrichtsbeobachtungen mit je einem anschließenden stimulated recall explorativ erfasst. Die Probanden setzten sich überwiegend heuristisch mit MILQ auseinander und implementierten vor allem Elemente auf Sichtstrukturebene im Unterricht, die konform zu ihren bisherigen Vorstellungen waren. Dadurch wurde das fachdidaktische Innovationspotential nicht ausgeschöpft. Bezeichnend ist, dass der empirische Wirksamkeitsnachweis von MILQ für die Beurteilung der Lehrkräfte nicht relevant war, was aus theoretischer Sicht bislang als ein zentrales Argument der Bereitstellungsstrategie zur Implementierung fachdidaktischer Innovation angenommen wurde.
Keywords: General Medicine

Learning to Plan by Learning to Reflect?—Exploring Relations between Professional Knowledge, Reflection Skills, and Planning Skills of Preservice Physics Teachers in a One-Semester Field Experience - Vogelsang, Christoph; Kulgemeyer, Christoph; Riese, Josef (Education Sciences)
Following concepts describing lesson planning as a form of anticipatory reflection, preservice physics teachers’ reflection skills are assumed to be positively connected with their planning skills. However, empirical evidence on this is scarce. To explore how relations between these specific skills change over the course of a field experience controlling for influences of professional knowledge, we conduct a pre-post field study with N = 95 preservice physics teachers in a one-semester field experience. Content knowledge (CK) and pedagogical content knowledge (PCK) (paper-and-pencil tests), and reflection and planning skills (standardized performance assessments) were assessed before and after the field experience. Path analyses revealed almost no influence of reflection skills on planning skills. Reflections skills did not contribute to preservice teachers planning skills beyond knowledge, indicating both constructs might represent rather independent abilities. The results show the need for further development of models describing the development of teachers’ professional knowledge and skills in academic teacher education and for the development of concepts for a better integration of reflection and lesson planning in field experiences.
Keywords: Public Administration; Developmental and Educational Psychology; Education; Computer Science Applications; Computer Science (miscellaneous); Physical Therapy; Sports Therapy and Rehabilitation

How to Teach a Teacher: Challenges and Opportunities in Physics Teacher Education in Germany and the USA - Van Dusen, Ben; Vogelsang, Christoph; Taylor, Joseph; Cauet, Eva (Physics Education)

Surface Instability Modulates Cortical Information Processing In Multi-Joint Compound Movements - Lehmann, Tim; Visser, Anton; Havers, Tim; Büchel, Daniel; Baumeister, Jochen (Medicine &Science in Sports& Exercise)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Changes In Eeg Microstate Patterns Following Exhaustive Treadmill Exercise When Employing Reduced Channel Resolution - Büchel, Daniel; Allen, Carlos; Lehmann, Tim; Sandbakk, Øyvind; Baumeister, Jochen (Medicine &Science in Sports& Exercise)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Hydrogel-Based Biosensors - Völlmecke, Katharina; Afroz, Rowshon; Bierbach, Sascha; Brenker, Lee Josephine; Frücht, Sebastian; Glass, Alexandra; Giebelhaus, Ryland; Hoppe, Axel; Kanemaru, Karen; Lazarek, Michal; Rabbe, Lukas; Song, Longfei; et al. (Gels)
There is an increasing interest in sensing applications for a variety of analytes in aqueous environments, as conventional methods do not work reliably under humid conditions or they require complex equipment with experienced operators. Hydrogel sensors are easy to fabricate, are incredibly sensitive, and have broad dynamic ranges. Experiments on their robustness, reliability, and reusability have indicated the possible long-term applications of these systems in a variety of fields, including disease diagnosis, detection of pharmaceuticals, and in environmental testing. It is possible to produce hydrogels, which, upon sensing a specific analyte, can adsorb it onto their 3D-structure and can therefore be used to remove them from a given environment. High specificity can be obtained by using molecularly imprinted polymers. Typical detection principles involve optical methods including fluorescence and chemiluminescence, and volume changes in colloidal photonic crystals, as well as electrochemical methods. Here, we explore the current research utilizing hydrogel-based sensors in three main areas: (1) biomedical applications, (2) for detecting and quantifying pharmaceuticals of interest, and (3) detecting and quantifying environmental contaminants in aqueous environments.
Keywords: Polymers and Plastics; Organic Chemistry; Biomaterials; Bioengineering

Hyphenation of ultra-high-performance liquid chromatography and ion mobility mass spectrometry for the analysis of sequence-defined oligomers with different functionalities and tacticity - Berg, Marie-Theres; Herberg, Artjom; Kuckling, Dirk (International Journal of Polymer Analysis and Characterization)
In recent years, sequence-defined oligomers (SDOs) gained increasing interest due to their perfectly controlled molecular structure, thus providing defined properties. In order to tune the properties, different functionalities need to be incorporated into the oligomers and the chain tacticity needs to be controlled. Beside the synthesis of SDOs, suitable methods need to be found to analyze the molecular structure. In this work, oligomers exhibiting an alternating or block-wise sequence of side chain functionalities were analyzed using a hyphenation of ultra-high-performance liquid chromatography and electrospray ionization mass spectrometry enhanced by ion mobility separation (IMS). Moieties in the side chains were varied according to polarity and bulkiness. Moreover, chain tacticity was varied. Drift times in the IMS cell and the corresponding collision cross section (CCS) values were shown to be individual parameters allowing the identification of SDOs, even in the case that SDO structures only differ in sequence or tacticity of side chain functionalities. Thus, a library of CCS values was obtained as reference used for the analysis of complex mixtures of SDOs.
Keywords: Ultra-high-performance liquid chromatography; ion mobility separation; mass spectrometry; LC-MS hyphenation; sequence-defined oligomers

Quinuclidine-Immobilized Porous Polymeric Microparticles as a Compelling Catalyst for the Baylis–Hillman Reaction - Kumar, Amit; Kuckling, Dirk; Nebhani, Leena (ACS Applied Polymer Materials)
Poly(quinuclidin-3-yl methacrylate-co-divinylbenzene) microparticles having porous as well as nonporous morphology and varying contents of quinuclidine functionality were synthesized by distillation–precipitation polymerization. Further, the synthesized microparticles were explored to catalyze the Baylis–Hillman reaction between 4-nitrobenzaldehyde and acrylonitrile. Porous and nonporous microparticles functionalized with a catalytic moiety with a loading of 70% (labeled as P70 and NP70) were employed to optimize reaction parameters such as water content, solvent, and temperature for the Baylis–Hillman reaction between 4-nitrobenzaldehyde and acrylonitrile. Using optimal conditions, the catalytic efficiency of porous and nonporous microparticles at different feed compositions was determined. Porous microparticles containing 70% of quinuclidine (P70) displayed 100% conversion within 16 h at 50 °C, while nonporous microparticles containing 70% of quinuclidine (NP70) displayed a relatively less catalytic conversion, which is attributed to their lower surface area. Furthermore, the catalytic activity of porous microparticles containing 70% of quinuclidine (P70) for the Baylis–Hillman reaction involving a variety of aryl aldehyde derivatives was determined, where the microparticles displayed impressive catalytic efficiency. In addition, the reusability of the microparticles functionalized with a catalytic moiety was evaluated for five cycles of catalytic reaction.
Keywords: distillation−precipitation polymerization; porous microparticles; heterogeneous catalysis Baylis−Hillman reaction; reusable catalyst

Branching analysis of β-cyclodextrin-based poly(N-isopropylacrylamide) star polymers using triple detection SEC - Herberg, Artjom; Kuckling, Dirk (International Journal of Polymer Analysis and Characterization)
For the first time, poly(N-isopropylacrylamide) (PNIPAAm) star polymers with a β-cyclodextrin core are characterized in detail by size-exclusion chromatography (SEC) with triple detection to experimentally verify the number of arms. A combination of a refractive index detector, multi-angle laser light scattering detector, and an online-viscosimeter was used for branching analysis. At first, the SEC system was calibrated and the detector setup was validated using linear polystyrene reference polymers. The applicability of the established triple detection SEC for branching analysis was shown by the analysis of two commercially available polystyrene star polymers. Due to the high molar masses of the star polymers, both the contraction ratio g and g′ could be determined independently, thus allowing the calculation of the viscosity shielding ratio ε. Finally, the branching analysis of the PNIPAAm star polymers could experimentally confirm the assumed arm number of up to 21 arms. Moreover, an increasingly compact molecular structure and the influence of the arm number on the viscosity shielding ratio could be shown.
Keywords: Size-exclusion chromatography; triple detection; branching analysis; star polymers; poly(N-isopropylacrylamide); β-cyclodextrin

Selective area heteroepitaxy of InAs nanostructures on nanopillar-patterned GaAs(111)A - Riedl, Thomas; Kunnathully, Vinay S.; Verma, Akshay Kumar; Langer, Timo; Reuter, Dirk; Büker, Björn; Hütten, Andreas; Lindner, Jörg (Journal of Applied Physics)
A process sequence enabling the large-area fabrication of nanopillar-patterned semiconductor templates for selective-area heteroepitaxy is developed. Herein, the nanopillar tops surrounded by a SiN x mask film serve as nanoscale growth areas. The molecular beam epitaxial growth of InAs on such patterned GaAs[Formula: see text]A templates is investigated by means of electron microscopy. It is found that defect-free nanoscale InAs islands grow selectively on the nanopillar tops at a substrate temperature of 425 °C. High-angle annular dark-field scanning transmission electron microscopy imaging reveals that for a growth temperature of 400 °C, the InAs islands show a tendency to form wurtzite phase arms extending along the lateral [Formula: see text] directions from the central zinc blende region of the islands. This is ascribed to a temporary self-catalyzed vapor–liquid–solid growth on [Formula: see text] B facets, which leads to a kinetically induced preference for the nucleation of the wurtzite phase driven by the local, instantaneous V/III ratio, and to a concomitant reduction of surface energy of the nanoscale diameter arms.
Keywords: General Physics and Astronomy

Size‐Dependent Strain Relaxation in InAs Quantum Dots on Top of GaAs(111)A Nanopillars - Riedl, Thomas; Kunnathully, Vinay; Trapp, Alexander; Langer, Timo; Reuter, Dirk; Lindner, Jörg (Advanced Materials Interfaces)
Keywords: Mechanical Engineering; Mechanics of Materials

Wie können Erklärvideos zum Erwerb physikalischen Konzeptwissens beitragen? - Hörnlein, Madeleine; Kulgemeyer, Christoph